A Model for the High-temperature Origin and Paradoxical Distribution of Pegmatites in Mafic Plutons, Smartville Complex, California. (16th February 2018) - Beard, James S; Scott, Sean R
Abstract: The distribution of pegmatitic rocks in the zoned gabbro–diorite plutons of the late Jurassic Smartville Complex is counter-intuitive. Whereas pegmatitic gabbros are common in mafic cumulate olivine gabbros within the zoned plutons, they appear to be absent from the more evolved gabbros and diorites. We argue that this paradox is resolved by examining the crystallization and temperature history of the rocks in question. The evolved rocks in the plutons consist of two-pyroxene hornblende biotite gabbro and diorite. The amphibole in these rocks occurs as a partial replacement of pyroxene that forms as a consequence of the incongruent crystallization reaction generalized as amphibole ± quartz ± plag1 = pyroxene + hydrous melt ± plag2 [reaction (1)]. This is a vapor-absent reaction that can buffer melt water content during crystallization and conceivably preclude water saturation altogether. Experimental evidence places the onset of the incongruent formation of amphibole at c . 900°C. In contrast, amphibole and other hydrous phases occur only in trace amounts in the cumulate olivine gabbros. The water-buffering reaction is not encountered during crystallization, the intercumulus melt proceeds to water saturation, and high-temperature plagioclase–pyroxene pegmatites form. We argue that the primary role for undercooling favored for the formation of granitic pegmatites is not likely to be applicable to the Smartville gabbro pegmatites. As crystallization of the gabbro pegmatite proceeds, the amphibole-in boundary is eventually reached and incongruent crystallization of amphibole occurs. Nevertheless, once water saturation occurs, it is irreversible, and is eventually manifested by the low-temperature deuteric alteration associated with the pegmatites. In short, we argue that pegmatite formation in the Smartville gabbros, and probably many other gabbroic plutons, reflects water saturation of a magma at high temperature, estimated here at >900°C. In systems where reaction (1) is attained prior to water saturation, pegmatite formation may be delayed until late in the crystallization history or precluded altogether. MELTS modeling of basalt crystallization suggests a solution to the paradox, indicating that the difference between the two systems can reflect equilibrium versus fractional crystallization. Equilibrium crystallization of trapped, intercumulus melt favors high-temperature crystallization and water saturation and, hence, pegmatite formation. Fractional crystallization, for example in an open-system magma chamber, favors lower-temperature crystallization and permits reaction (1) to proceed, inhibiting water saturation and preventing pegmatite formation. The open-system nature of the fractionating magma chamber might also allow escape of volatiles at its margins, with the lower volatile content then communicated to the magma as a whole as the system convects or otherwise mixes.